Attempting developmental regionalism through AFTA : the domestic politics - domestic capital nexus - Helen E. S. Nesadurai (2009)
The relationship of regionalism to globalisation is modelled in the literature either as open regionalism aimed at integration with the global market or as a project of resistance to global market forces. Neither of these ideal-type models adequately accounts for an empirical puzzle associated with the ASEAN Free Trade Area (AFTA). Althought AFTA is acknowledged as a project of open regionalism aimed at attracting FDI to Southeast Asian region, its member surprisingly chose to accord foreign investors full market access and national treatment privileges at least ten years later than to ASEAN national investors in AFTA's investment liberalisation component programme. How do we explain this seeming contradition? By making a conceptual distinction between foreign-owned and domestic-owned capital, a distinction that is particularly salient in the Southeast Asian context where domestic-owned, often 'emerging' capital performs vital social/politial roles and whose survival is crucial in sustaining elite rule, this paper advances a third model of the globalisation-regionalism relationship. Developmental regionalism, which draws on stategic trade theory from the International Economics discipline, describes and approach to regionalism in which an initial period of partial and temporary resistance to global competition is employed to build up domestic firms able to eventually engage in global competition. In particular, it was to preserve domestic businesses that were closely allied with members of the political/ruling elite that led certain member goverments in ASEAN to advocate a developmental role for AFTA through its investment liberalisation programme, while still using the regional tariff liberalisation component programme as the 'carrot' to attract FDI.